1984
DOI: 10.1016/0022-3093(84)90139-x
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction studies of natural glasses

Abstract: A neutron diffraction investigation has been carried out of the structures of several naturally occurring glasses, viz. Libyan Desert glass, a Fulgurite, Wabar glass-. Lechatel ierite from Canon Diablo, a Tektite, Obsidian (3 samples), and Macusani glass. Libyan Desert sand has also been examined, together with crystalline a-quartz and a-cristobalite. A comparison of data for-the natural glasses and synthetic vitreous silica (SpectrosM "6") in both reciprocal and real space allows a categorisation into Silicas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Its rare abundance is the reason of particular desire from both scientists and jewellers. Its beauty and value was already appreciated in the time of pharaohs or even earlier, by prehistoric humans [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its rare abundance is the reason of particular desire from both scientists and jewellers. Its beauty and value was already appreciated in the time of pharaohs or even earlier, by prehistoric humans [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The precious pieces are scattered over an area of 6500 km 2 in the Western Desert of Egypt, south-east from the border with Libya (Fig.1). Herodot called everything to the west of the Nile as Libyan Desert and this is probably how the material got its name [6].…”
Section: Introductionmentioning
confidence: 99%
“…Taylor and Brown [207]). Wright et al [209] made distinctions between silica (fulgurite) and silicate glasses (obsidian and tektite) based on neutron diffraction measurements. Okuno et al [210] studied molten and untreated obsidian and also found that the basic structures of samples may be explained by the "stuffed tridymite" model.…”
Section: Structure Of Silicate Glassesmentioning
confidence: 99%
“…are interconnected to form an unbounded 3D lattice via co‐edge or co‐top within the internal framework of BS. [ 26 ] Because of the cationic isocrystalline substitution within these structural units, an excess of negative charges is produced. To maintain electrical neutrality within the internal system, the lateral area of the structural units in BS is compensated by cations (such as Ca 2+ , K + , Na + , etc.)…”
Section: Introductionmentioning
confidence: 99%